NON-STATUTORY EXECUTIVE POWERS: ASSESSING GLOBAL CONSTITUTIONALISM IN A STRUCTURAL-INSTITUTIONAL CONTEXT. Issue 1 (19th December 2014) - Unknown
Abstract: This article analyses the source, nature, and use of unilateral, non-statutory executive powers, frequently employed as a governance tool but rarely studied in a comparative context. Exercised in the absence of direct statutory authorization, such powers are often invoked by executives in emergency and foreign affairs contexts, but are equally central to domestic policy-making. Unilateral executive power challenges two central democratic values that support the separation of powers ideal: representation and deliberation. Different structural treatments of these powers are considered through a comparison of three constitutional regimes, those of the United States, the United Kingdom and Israel. Despite material structural differences between these systems, the emerging patterns are similar enough to support the argument that direct law-making by the executive is an unavoidable element of the political sphere. Developing a template for comparison analysis, this article shows that a pattern of functional convergence has emerged, unsupported by overt transplantation or borrowing between these systems. The results set a possible challenge to the growing recognition of global world constitutionalism, at least in structural-institutional contexts.